2015
DOI: 10.11648/j.ajpn.20150306.13
|View full text |Cite
|
Sign up to set email alerts
|

Psychotropic Medication Use in Children and Adolescents with Mental Retardation (MR)

Abstract: Abstract:Background: The aim of this study was to assess the medication use in children and adolescents with mental retardation (MR) retrospectively in a cross-sectional study. Method: Between June and December 2013, records of the children and adolescents admitted by our policlinic were retrospectively evaluated and those who had MR diagnosis were analyzed. Results: Male sex was found as statistically related to the presence of psychiatric comorbidity and the pervasive developmental disorders (PDD). At least … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…The prevalence in this study is consistent with cross-sectional data reported from adolescent out-patients in Turkey (20.4%). 23 …”
Section: Discussionmentioning
confidence: 99%
“…The prevalence in this study is consistent with cross-sectional data reported from adolescent out-patients in Turkey (20.4%). 23 …”
Section: Discussionmentioning
confidence: 99%